An Engineered Endomorphin-2 Gene for Morphine Withdrawal Syndrome - Wu, Fei-xiang (PLoS One, 2016)
An optimal therapeutics to manage opioid withdrawal syndrome is desired for opioid addiction treatment. Down-regulation of endogenous endomorphin-2 (EM2) level in the central nervous system after continuous morphine exposure was observed, which suggested that increase of EM2 could be an alternative novel method for opioid dependence. As a short peptide, the short half-life of EM2 limits its clinical usage through conventional administration. In the present study, we engineered an EM2 gene using a signal peptide of mouse growth factor for an out-secretory expression of EM2 and an adenovirus as a vector, which ultimately sustained the release of EM-2. After administration of the adenovirus in central nervous system, a sustained increase of EM2 level in the cerebral spinal fluid (CSF) was observed along with a reduction of morphine withdrawal syndrome. These findings suggest that the engineered EM2 gene delivered to the central nervous system could be a novel therapeutics for withdrawal syndrome in opioid dependent subjects.